2016
DOI: 10.1371/journal.pntd.0004529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR Approaches for Detection of Bartonella bacilliformis in Blood Samples

Abstract: BackgroundThe lack of an effective diagnostic tool for Carrion’s disease leads to misdiagnosis, wrong treatments and perpetuation of asymptomatic carriers living in endemic areas. Conventional PCR approaches have been reported as a diagnostic technique. However, the detection limit of these techniques is not clear as well as if its usefulness in low bacteriemia cases. The aim of this study was to evaluate the detection limit of 3 PCR approaches.Methodology/Principal FindingsWe determined the detection limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The conventional PCR assay used in this study was designed to detect Bartonella genus DNA but is also able to amplify phylogenetically related microorganisms such as Brucella spp. 22 The conventional PCR detection of Mesorhizobium spp., nitrogen-fixing bacteria belonging to the order Rhizobiales, in L. maranonensis is not surprising. These microorganisms are closely related to Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional PCR assay used in this study was designed to detect Bartonella genus DNA but is also able to amplify phylogenetically related microorganisms such as Brucella spp. 22 The conventional PCR detection of Mesorhizobium spp., nitrogen-fixing bacteria belonging to the order Rhizobiales, in L. maranonensis is not surprising. These microorganisms are closely related to Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, del Valle et al [ 22 ] detected 21 acute Carrion’s disease cases analyzing 113 previously diagnosed as negative patients using a Bartonella -specific 16S rRNA based PCR. Nonetheless, further studies showed the potential limitation of this technique to detect asymptomatic carriers [ 23 ]. The use of RT-PCR has also been studied [ 16 ], 14 positive acute being detected cases among 63 previously negative children.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products were analyzed by sequencing in both the forward and reverse directions were applied according to currently recommended methods. [8][9][10] Variant detection was scored using publicly available variant databases for CF such as the Cystic Fibrosis Mutation Database (http://www.genet.sickkids.on.ca/ CFTR /Home.html) and The Human Gene Mutation Database -Professional Edition. (http://www.hgmd.…”
Section: Cftr Identificationmentioning
confidence: 99%